An evaluation of the information architecture of the UCT Library web site - Mvungi, Susan Haikaeli (Library and Information Studies Centre (LISC), 2022)
Web users are becoming more critical of the web sites they use. This dissertation evaluates the information architecture of the academic library web site at the University of Cape Town. The evaluation of the information architecture of an academic library web site is important because the web site functions as an international gateway to the institution's valuable library resources. A library may therefore be judged on the basis of its web site. It is no wonder that a lot of effort is put into ensuring a well-designed web site. A multi-approach evaluation was completed to evaluate the library web site. Firstly, a formal usability test was conducted with five users to establish the required site structure and to identify any possible problems with the usability of the site. Secondly, a heuristic evaluation with an expert was conducted to test the web site content, information architecture, and navigation design. Thirdly, a closed card sort analysis with ten participants was completed in order to establish the required site structure and terminology for the potential web site re-design. Fourthly, a comparative analysis of the previous versions of the university library web site was done to highlight the main differences and improvements. Reviewing "prior-art'1/previous versions of any web site guarantees the development of an improved information architecture. In addition to the aforementioned evaluation techniques, the study recommended the use of a requirements document that was developed for the purposes of this study that details a set of standard guidelines for the academic library site maintenance. In an attempt to improve the navigation problems identified on the library web site, a site map was developed for the web site as well. 11l This research found that the library web site had an overall usable web site with users rating their satisfaction with the site between good and very good. The site however exhibited a few problems with the terminology used, there were also problems identified with the navigation design. Issues relating to identifying specific information were also identified. This dissertation presents recommendations to handle the aforementioned problems. The study also encourages continual web site evaluation.